Anthraquinone as an additive in alkaline pulping with special reference to semi-alkaline sulphite pulping of pine timber - Raubenheimer, S. J.(Stephanus Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Wood Science)) -- University of Stellenbosch, 1980.